LITERATURE REVIEW: PLACENTAL MORPHOLOGY OF PREGNANT WOMAN WITH THE COVID-19 - Siti Choirul Dwi Astuti (POLTEKKES KEMENKES JAYAPURA, 2022)
Placental disruption is an essential factor contributing to intrauterine fetal growth. Pregnant women who have been infected with Covid-19 will experience complications. One of the consequences of pregnant women have been infected with Covid-19 will cause delays in neural development in babies from the time they are in the womb. Delayed neural development in utero is associated with placental disorders. This study aims to review the literature on the placental product in pregnant women with Covid-19. The research was conducted by searching for journals on scientific sites using Covid-19 and Placenta. The study used articles published from 2018 to 2022. The results were 32 articles that stated that pregnant women with confirmed Covid-19 would have lower placental weight, dark placental color, and abnormal umbilical cord insertion. In conclusion, abnormal placentas were found in pregnant women with Covid19, but the Placenta also resembled the Placenta in women with diabetes and hypertension. More extensive studies are needed to elucidate the contribution of impaired placentation to delayed neurodevelopment in Covid-19 cases. Keywords: Covid-19, Pregnant mother, Placenta